RELIGIOUS DIGITAL LITERACY IN ISLAMIC HIGHER EDUCATION: STUDENT-PERCEIVED BENEFIT - Usman Usman; Syarifah Halifah; Ahmad Abbas; Syamsidar Syamsidar (Sosiohumaniora, 2023)
Digital media tends to be used to deliver literacy regarding radicalism that can develop on campus. Students in Islamic Higher Education are considered as important subjects in using digital literacy.The purpose of this research is to demonstrate religious digital literacy perceived by students in Islamic Higher Education. The type of this research was qualitative using a phenomenological approach. Research objects were Islamic Higher Education in South Sulawesi consisting of IAIN Parepare, UM Parepare, as well as STAI DDI in Parepare, Pinrang and Sidrap. The informants were students from the Students Executive Board and Da’wah Units. An ambassador of Digital Literacy in the Library and Archives Office of South Sulawesi also became an informant in this research. The result demonstrates that religious digital literacy held in Islamic Higher Education in South Sulawesi greatly contributes to the student’s perspective change in comprehending information disruption and radicalism. Campuses conduct religious moderation events through workshops and the digital space. Otherwise, students use various digital sources to strengthen information. The source of religious digital literacy derives from information which is spread on WhatsApp, Facebook. YouTube, Telegram and Instagram. Therefore, the emergence of Islamic Higher Education in South Sulawesi can lead students to cope with information disruptions, and prevent the action of radicalism and fanaticism in the religion.